Sustainable Development after Covid-19: Environmental Issues and Challenges - Dr. Anupa Singh (International Journal of Engineering and Management Research, 2020)
In a few short months, COVID-19 has morphed from a dangerous regional health threat to an all-consuming global pandemic and economic disaster. The COVID-19 pandemic is considered as the most crucial global health calamity of the century and the greatest challenge that the humankind faced since the 2nd World War. In December 2019, a new infectious respiratory disease emerged in Wuhan, Hubei province, China and was named by the World Health Organization as COVID-19 (coronavirus disease 2019).According to the report of the World Health Organization (WHO as of May26, 2020), the current outbreak of COVID-19, has affected over 5,404,512 people and killed more than 343,514 people in more than 200 countries throughout the world. COVID-19’s rapid spread has had far-reaching implications on the everyday lives of people posing enormous health, economic, environmental and social challenges to the entire human population. To some extent COVID-19 outbreak may be considered as an indirect consequence of global environmental changes. The environmental consequences of the crisis have been both positive and negative. Overall, the crisis may thus have no permanent environmental effects. Attention must be given to threats on the environment and natural resource bases as a result of the coronavirus pandemic and consequential social and economic impacts. Effective responses and recovery plans will therefore need to take into account the pandemic’s multiple dimensions, as well as its deep roots in environmental stresses and global mobility. This paper describes the impact of COVID-19 on the global environment, and the global strategies for the prevention and control of the disease by not only prioritizing social, economic and environmental concerns but also ensuring that sustainability post COVID-19 encompasses healthy living for all.